Wealth and sexual behaviour among men in Cameroon - Nana Philip; Mbu Robinson E; Wiysonge Charles S; Kongnyuy Eugene J; Kouam Luc (BMC, 2006)
Abstract Background The 2004 Demographic and Health Survey (DHS) in Cameroon revealed a higher prevalence of HIV in richest and most educated people than their poorest and least educated compatriots. It is not certain whether the higher prevalence results partly or wholly from wealthier people adopting more unsafe sexual behaviours, surviving longer due to greater access to treatment and care, or being exposed to unsafe injections or other HIV risk factors. As unsafe sex is currently believed to be the main driver of the HIV epidemic in sub-Saharan Africa, we designed this study to examine the association between wealth and sexual behaviour in Cameroon. Methods We analysed data from 4409 sexually active men aged 15-59 years who participated in the Cameroon DHS using logistic regression models, and have reported odds ratios (OR) with confidence intervals (CI). Results When we controlled for the potential confounding effects of marital status, place of residence, religion and age, men in the richest third of the population were less likely to have used a condom in the last sex with a non-spousal non-cohabiting partner (OR 0.43, 95% CI 0.32-0.56) and more likely to have had at least two concurrent sex partners in the last 12 months (OR 1.38, 95% CI 1.12-1.19) and more than five lifetime sex partners (OR 1.97, 95% CI 1.60-2.43). However, there was no difference between the richest and poorest men in the purchase of sexual services. Regarding education, men with secondary or higher education were less likely to have used a condom in the last sex with a non-spousal non-cohabiting partner (OR 0.24, 95% CI 0.16-0.38) and more likely to have started sexual activity at age 17 years or less (OR 2.73, 95% CI 2.10-3.56) and had more than five lifetime sexual partners (OR 2.59, 95% CI 2.02-3.31). There was no significant association between education and multiple concurrent sexual partnerships in the last 12 months or purchase of sexual services. Conclusion Wealthy men in Cameroon are more likely to start sexual activity early and have both multiple concurrent and lifetime sex partners, and are less likely to (consistently) use a condom in sex with a non-spousal non-cohabiting partner. These unsafe sexual behaviours may explain the higher HIV prevalence among wealthier men in the country. While these findings do not suggest a redirection of HIV prevention efforts from the poor to the wealthy, they do call for efforts to ensure that HIV prevention messages get across all strata of society.